2020
DOI: 10.1038/s41598-020-59622-y
|View full text |Cite
|
Sign up to set email alerts
|

Study of glycosylation of prostate-specific antigen secreted by cancer tissue-originated spheroids reveals new candidates for prostate cancer detection

Abstract: Prostate-specific antigen (PSA) is the most frequently used biomarker for the screening of prostate cancer. Understanding the structure of cancer-specific glycans can help us improve PSA assay. In the present study, we analysed the glycans of PSA obtained from culture medium containing cancer tissue-originated spheroids (CTOS) which have similar characteristics as that of the parent tumour to explore the new candidates for cancer-related glycoforms of PSA. The glycan profile of PSA from CTOS was determined by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 46 publications
(36 reference statements)
1
18
0
Order By: Relevance
“…Therefore, glycoproteins can be considered an ideal source for the early detection of cancers [ 22 ]. For instance, many cancer biomarkers in the clinic are glycoproteins, including CEA in CRC [ 6 ], carbohydrate antigen 19-9 (CA19-9) in gastrointestinal cancer [ 23 ], and prostate-specific antigen (PSA) in prostate cancer [ 24 ]. Lectin chromatography has been widely used to capture glycoproteins for MS analyses [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, glycoproteins can be considered an ideal source for the early detection of cancers [ 22 ]. For instance, many cancer biomarkers in the clinic are glycoproteins, including CEA in CRC [ 6 ], carbohydrate antigen 19-9 (CA19-9) in gastrointestinal cancer [ 23 ], and prostate-specific antigen (PSA) in prostate cancer [ 24 ]. Lectin chromatography has been widely used to capture glycoproteins for MS analyses [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…PSA is a glycoprotein whose glycan significantly changes with PCa development/progression [ 4 , 5 ]. Glycosylation is a driver for cancer development/progression [ 11 , 12 ], and thus, glycoprofiling PSA could outperform currently used PCa tests [ 13 ]. Murphy et al found that glycan analysis, in combination with other approaches (DNA analysis, transcriptomics, and proteomics), is a robust tool for tumor stratification [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, fuc-PSA was not able to better stratify aggressive and non-aggressive PCa in comparison to standard methods (%-Free PSA and total PSA). Glycans of PSA were also investigated in PCa tissue-originated spheroids (CTOS) [ 75 ]. The cardinal principle of this study was that CTOS-derived PSA is considered to reflect glycan structures of the patient’s tumour.…”
Section: Prostate Specific Antigenmentioning
confidence: 99%